The effect of chlorhexidine and triclosan on undisturbed plaque formation for 72 hours duration - Erry Mochamad Arief; Noor Dina Binti Adnan; Raja Azman Raja Awang (DiscoverSys Inc., 2010)
Plaque control is the main method for preventing periodontal diseases. Chlorhexidineia a gold standard mouthrinse but it has a side effect which limits its use. Triclosanwhich does not have side effects was used to evaluate its efficacy againstchlorhexidine. This experiment aimed to evaluate the effect of chlorhexidine andtriclosan on undisturbed plaque formation for 72 hours. Two groups, chlorhexidineand triclosan, respectively consists of 14 volunteers refrained from all mechanicaloral hygiene measures for the following 72 hours and rinsed instead twice daily for 1minute with 15 mL of either chlorhexidine or triclosan. The plaque accumulation wasassessed after 24, 48 and 72 hours using Modified Quigley-Hein Score. The medianplaque score between both groups on day 1 was not significantly different (p= 0.625),but the score on day 2 and day 3 were significantly different (p= 0.007 and 0.017respectively). The score between day 1 and day 3 on subjects using chlorhexidine wasnot significantly different (p= 0.109) unlike on subjects using triclosan (p= 0.003).The conclusion was chlorhexidine is more effective in controlling plaque formationcompared to triclosan.